Hubungan Peran Petugas Kesehatan dengan Pemeriksaan Haemoglobin Ibu Hamil di Puskesmas Rumbio Jaya - Sari, Rosyulia; Harahap, Dewi Anggriani; Parmin, Joria (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Examination of the blood hemoglobin level of pregnant women is carried out at least once in the first trimester and once in the third trimester. The goal is to determine whether or not anemia during pregnancy because anemia can affect the process of fetal growth and development in the womb. The purpose of this study was to determine the relationship between the role of health workers and hemoglobin examination at the Rumbio Jaya Health Center. The research design was cross sectional. The population of this study were all pregnant women in the first and third trimesters, with a sample of 54 people, the sampling technique was accidental sampling. The measuring instrument used is a questionnaire. Analysis of the data used is univariate and bivariate. Univariate analysis revealed that from 54 officers there were 32 people (59.3%) who did not play a role while 22 people (40.7%) had a role. Bivariate results with a P-value of 0.014 <0.05, it means that there is a relationship between the role of health workers by checking hemoglobin in pregnant women at the Rumbio Jaya Health Center, by checking hemoglobin in pregnant women at the Rumbio Jaya Health Center. It is hoped that health workers can provide information about the importance of carrying out Hb checks in pregnant women and increase knowledge of pregnant women through counseling activities in Pregnant Women Classes and health facilities